PERBEDAAN PERILAKU ETIS DAN TEKANAN KERJA PERSPEKTIF GENDER DALAM AUDIT JUDGMENT LAPORAN KEUANGAN HISTORIS DAN KOMPLEKSITAS TUGAS - INDAH PARAMITASARI ASTUTIK (Trunojoyo University of Madura, 2008)
The purpose of this research was to examine the differences of auditor’s ethic behaviour and work stress when they conducted audit assignment.. The population was Public Accounting Office in Surabaya. This research using questionnare, from 254 questionnare which sent, was responded 97 questionnare and could be analyze was 54 questionnaire. Data analysis used SPSS 12 for examining reliability, validity, and independent samples t-test. The research’s result indicated that there was a significant difference between male auditor and female auditor in the ethic behaviour and work stress. The other research’s result indicated that married status, education level, working position, and working time had no significant difference in the ethic behaviour and work stress.